Significance of Coronary Calcification for Prediction of Coronary Artery Disease and Cardiac Events Based on 64-Slice Coronary Computed Tomography Angiography - Liu, Yuan-Chang; Sun, Zhonghua; Tsay, Pei-Kwei; Tiffany, Chan; Hsieh, I-Chang; Chen, Chun-Chi; Wen, Ming-Shien; Wan, Yung-Liang (Hindawi Publishing Corporation, 2013)
This work aims to validate the clinical significance of coronary artery calcium score (CACS) in predicting coronary artery disease(CAD) and cardiac events in 100 symptomatic patients (aged 37–87 years, mean 62.5, 81 males) that were followed up for a mean of 5 years. Our results showed that patients with CAD and cardiac events had significantly higher CACS than those without CAD and cardiac events, respectively. The corresponding data were 1450.42 ± 3471.24 versus 130 ± 188.29 (P < 0.001) for CAD, and1558.67 ± 513.29 versus 400.46 ± 104.47 (P = 0.031) for cardiac events. Of 72 patients with CAD, cardiac events were found in 56 (77.7%) patients. The prevalence of cardiac events in our cohort was 13.3% for calcium score 0, 50% for score 11–100, 56% for score 101–400, 68.7% for score 401–1,000, and 75.0% for score >1000. Increased CACS (>100)was also associated with an increased frequency of multi-vessel disease. Nonetheless, 3 (20%) out of 15 patients with zero CACS had single-vessel disease. Significant correlation (P < 0.001) was observed between CACS and CAD on a vessel-based analysis for coronary arteries. It is concluded that CACS is significantly correlated with CAD and cardiac events.